Application of 3Å Synthetic Zeolite as an Adsorbent to Reduce the Hygroscopicity of B40 Biodiesel - Sovia El Rafiqa; Eddy Ibrahim; Muhammad Rendana; M. Taufik Toha; Maulana Yusuf; Rahmat Wahyudi Putra (International Journal of Engineering Continuity, 2025)
This study investigates the effectiveness of synthetic 3Å zeolite and silica in reducing water content in B40 biodiesel, a high-FAME blend prone to moisture absorption. Adsorption tests were performed using varying adsorbent masses (1.5–7.5 g) and contact durations (60–180 minutes), with water content measured via Karl Fischer titration. Both materials significantly reduced moisture levels, with the highest reduction observed using 7.5 g of silica after 180 minutes. Multiple linear regression analysis confirmed that adsorbent mass and contact time had statistically significant effects (p < 0.001), while adsorbent type did not (p = 0.088), indicating that performance differences were not consistent across all conditions. These results refine the understanding of adsorbent behavior in biodiesel drying and support more informed selection based on operational priorities such as adsorption speed or reusability. This research contributes to the optimization of non-thermal moisture control strategies in biodiesel purification and highlights the need for future studies on adsorbent regeneration and scale-up feasibility.